CNCP Fractions and in Vitro Rumen Fermentation of Straw Based Total Mixed Rations Supplemented with Leucaena leucocephala Leaves - Rajvaidya, Saurabh; Mohini, Madhu; Sarkar, Srobana; Mondal, Goutam; Pandita, Sujata (Indian Journal of Animal Nutrition, 2018)
An in vitro study was conducted to evaluate the effect of the different ratios of Leucaena (Leucaena leucocephala) leaves (L), wheat straw (W) and concentrate mixture (C) on total gas production, methanogenic potential and other rumen fermentation parameters using in vitro gas production technique. Four total mixed ration (TMR) were prepared using dried ground samples of W, C and L: WC (90W: 10C), WCL10 (80W: 10C: 10L), WCL25 (65W: 10C: 25L) and WCL50 (40W: 10C: 50L). For estimation of fermentation parameters, TMR samples (200 mg) were incubated with 30 mL buffered rumen liquor at 39Â±0.5ÂºC for 24 h. As the level of Leucaena leaves increased in the substrate, total gas production increased (P<0.05) while CH4 production (mL/100 mg DDM) decreased (P<0.05) by 15, 24 and 36% in WCL10, WCL25 and WCL50, respectively. In vitro DM and OM digestibility was also higher (P<0.05) as the levels of Leucaena increased in the ration. Thus, this study indicated that with the inclusion of Leucaena to straw based ration, there was improved utilization of nutrients and reduced methane production.